Rancang Bangun Sistem Informasi Monitoring, Evaluasi, dan Pembinaan Tata Kelola Sekolah Dasar Menggunakan Metode Waterfall - Fetrik Gutris; Muhammad Iqbal; Mia Rosmianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The implementation of monitoring, evaluation, and guidance for elementary school governance in the Regional Education Office still faces challenges in information management because data from schools has not yet been integrated, resulting in evaluation, guidance, and decision-making processes that are not yet effective. This study aims to design and develop a web-based information system to support the integrated management of monitoring, evaluation, and guidance using the Waterfall method, which includes needs analysis, design, implementation, testing, and conceptual maintenance. The research resulted in a system capable of linking the monitoring, evaluation, and guidance processes into a single operational mechanism for information management, so that monitoring results directly serve as the basis for conducting evaluations, while evaluation results serve as the basis for developing guidance without requiring reprocessing or transferring data to other media. Unlike similar systems, which generally still separate these three processes, the developed system forms a continuous information management cycle, thereby supporting data consistency and strengthening the Regional Office’s decision-making in overseeing elementary school governance. The results of Black Box Testing showed that all system functions operate in accordance with functional requirements, while User Acceptance Testing (UAT) achieved a user acceptance rate of 83%, indicating that the system is acceptable and supports users’ operational needs. Thus, this research not only produced a web-based information system but also offered an operational mechanism that integrates monitoring, evaluation, and guidance into a single information management cycle to support more effective oversight of elementary school governance.